PERANCANGAN BUSANA SIAP PAKAI DENGAN MATERIAL UTAMA TENUN SUMBA LAU PAHIKUNG BERDASARKAN ANALISIS KEBUTUHAN PASAR URBAN: DESIGNING READY-TO-WEAR CLOTHING WITH SUMBA LAU PAHIKUNG WOVEN MAIN MATERIAL BASED ON URBAN MARKET NEEDS ANALYSIS - Grace Carolline Sahertian; Sri Ningsih, Yosepin; Bahaduri, Berti Alia (Jurnal Dimensi Seni Rupa dan Desain, 2024)
Indonesia's diverse handicrafts include Lau Pahikung woven cloth from Sumba Island, East Nusa Tenggara. Lau means sarong in the local language, and Pahikung is a weaving technique for fabric patterns. This cloth, made using ikat and Pahikung dyeing, is crafted into sarongs for Sumba women. The research partners with the Sekar Kawung Foundation, supported by weavers in East Sumba, who use sustainable methods to create Lau Pahikung fabrics. These fabrics are transformed into urban product displays through market analysis. The analysis, incorporating Maslow's needs theory and Indonesia Trend Forecasting, leads to ready-to-wear fashion designs that cater to specific formal clothing needs, offering versatile contemporary styles.